Z KUŞAĞINDA SOSYAL MEDYANIN DİJİTAL PAZARLAMAYA ETKİSİ. - HORUZTEPE, Bilal Fatih (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2018)
Entered our lives with the advancements on information and communication technology, the social media, by accelerating the globalization process, has played a signifıcant role arising a generation that have same needs and characteristics ali över the world. Bom in information age and named as generation Z, this generation has an important place on social media usage. Understanding this new generation, which will become much more important for businesses as being more active in the market in near future, is quite signifıcant in terms of marketing discipline. In this study, it has been attempted to determine how buying behavior of generation Z individuals are affected in what way from social media.